Study on the individualized training programme of the middle player based on the statistical results offered by the "Data Volley" software - Harabagiu, N.; Pacuraru, A, (Gymnasium - Scientific Journal of Education, Sports and Health, 2019)
The use of the "Data Volley" software of statistical analysis in professional volleyball can offer many options of assessment and analysis, among which also the individual evaluation of a single player or of a single game position in turn. In the current case, that of the Middle Blocker. This programme of recording, assessment and analysis was designed to offer fast and precise information to coaches of all levels, by which to judge their team or the opposite team. The main objective of this study is to implement a programme of individualized training for the Middle Blocker, using statistical information, but also details obtained from the video evaluation of each technical element, and the capacity of putting into practice the tactical indications coming from the coach, that are specific for the Middle Blocker.